Recent advance in direct sp3 carbon-hydrogen bond functionalizations - Cai, Xiao-Hua; Jin, Jun; Xie, Bing (European Journal of Chemistry, 2016)
Direct and selective carbon-hydrogen bond functionalization has attracted enormous attention because it provides more efficient strategies for preparing valuable functional molecules from easily available substrates. Significant and exciting developments in functionalization of un-activation Csp3-H bonds have continuously been made over the past few decades. This review mainly summarizes recent advances on direct Csp3-H bond functionalization for the formation of C-C and C-heteroatom bond under transition-metal-catalysed and metal-free conditions.